Characterization of the Ca2+‐responsive signaling pathway in regulating the expression and secretion of cellulases in Trichoderma reesei Rut‐C30. Issue 3 (2nd March 2016) - Chen, Ling; Zou, Gen; Wang, Jingzhi; Wang, Jin; Liu, Rui; Jiang, Yanping; Zhao, Guoping; Zhou, Zhihua
Summary: Calcium signaling plays pivotal roles in the hyphal growth, conidiation, and osmosis sensitivity of fungi through the Ca 2+ /calmodulin‐calcineurin‐dependent pathway. This study found that an appropriate extracellular Ca 2+ concentration markedly stimulated the hyphal growth, cellulase production, and total protein secretion of the cellulase hyper‐producing strain, Trichoderma reesei Rut‐C30. Transcription analysis revealed upregulation of not only encoding genes of cellulases and the transcriptional activator XYR1 but also several genes encoding endoplasmic reticulum‐chaperones after Ca 2+ addition. The function of CRZ1, T. reesei c alcineurin‐r esponsivez inc finger transcription factor1, was further characterized by gene disruption. Electrophoretic mobility shift assays (EMSAs) in combination with chromatin immunoprecipitation (ChIP) verified that CRZ1 could bind directly to the upstream regions of xyr1 and cbh1 (cellobiohydrolase I‐encoding gene) in response to Ca 2+ . A DNase I footprinting assay identified its putative binding consensus site (5′‐[T/G]GGCG‐3′ or 5′‐GGGC[G/T]‐3′). EMSAs confirmed that CRZ1 competed for occupancy of the xyr1 promoter with another transcription factor, ACE1. These results revealed putative signaling pathways downstream of calcineurin in response to extracellular Ca 2+ involved in upregulation of cellulose degradation‐related genes, reflecting progress in the study of Ca 2+ signaling in filamentous fungi. This study also provides insight that will facilitate further improvement of (hemi‐)cellulase production by T. reesei . Abstract : The addition of Ca 2+ stimulates the expression of cellulase and hemicellulase genes, endoplasmic reticulum chaperones and xyr1 (global transcriptional activator of cellulases and hemicellulases) in Trichoderma reesei Rut‐C30. It was demonstrated that the transcription factor CRZ1 responds to extracellular Ca 2+ and further activates the expression of its downstream targets, xyr1 and several cellulase‐encoding genes (for example, cbh1 ), directly by binding to their upstream regions.